ANALISIS MUTU MADRASAH UNGGULAN DI ACEH: Studi di Madrasah Aliyah Ruhul Islam Anak Bangsa (MA RIAB) and Madrasah Aliyah Negeri (MAN) Model Banda Aceh - Ina Fauziana Syah (Universitas Islam Negeri Ar-Raniry, 2016)
This research focused on the deep analysis about the description of qualified Islamic School in Aceh. This research using qualitative research method, the data collected through interviews, observation and documentary study. Sample of this research are Madrasah Aliyah Ruhul Islam Anak Bangsa (MA RIAB) and Madrasah Aliyah Negeri (MAN) Model B. Aceh. This research found that MA RIAB and MAN Model are not fully qualified since they are not yet implementing the brandmark of qualification properly.